Legal Status Of Underage Children With Dual Citizenship Related To Inheritance - Permata Kumala, Cheryl; Anom Husodo, Jadmiko; Grahani Firdausy, Adriana (International Journal of Educational Research & Social Sciences, 2024)
The purpose of this study is to analyze the legal status of an immature child with dual citizenship. This type of research that is used is normative law research that investigates the systematics of law. This systematic research of law is carried out against the regulations of laws or laws written according to the topic that has been raised. The results of the research show that the legal status of a minor child with dual citizenship in connection with inheritance is to remain entitled to inherit the property of land in Indonesia without interference from others even though the status of the child still has 2 (two) citizenships and still has not been able to choose one of the nationalities between Indonesia or another country. Therefore, basically any citizen of the child/s descendants cannot prevent or remove the child's inheritance.